HISTORICAL ROOTS OF SOCIAL HARMONY AMONG MULTI-RELIGIOUS COMMUNITIES IN THE PETIK LAUT TRADITION OF CANDIKUSUMA VILLAGE - BALI: Jejak Historis Harmoni Sosial Masyarakat Multi Agama pada Tradisi Petik Laut di Desa Candikusuma, Bali - Diva, I Putu Diva Widanankara; I Wayan Putra Yasa; Desak Made Oka Purnawati (Santhet (Jurnal Sejarah Pendidikan Dan Humaniora), 2026)
This study aims to determine the background of the coastal community of Candikusuma Village in carrying out the sea harvest tradition, the forms of collaboration in the sea harvest tradition in Candikusuma Village, and aspects of character education that can be used to develop a history learning supplement in high school. This research is a qualitative study using descriptive methods. Informants in this study were selected by snowball sampling. The informants in this study were the Head of Candikusuma Village, the Head of the Banjar Tirtakusuma Environment, the head of the sea harvest committee, representatives of Hindu religious leaders, representatives of Islamic religious leaders, and representatives of Christian religious leaders. Research data were collected through interviews, observations, and documentation. The results of the study indicate that the background of the sea harvest tradition is carried out as a form of gratitude to God Almighty for the marine products obtained, as well as a request for safety, blessings, and smoothness in carrying out activities as fishermen. Forms of collaboration in the implementation of the sea harvest tradition are seen from the active involvement of the entire community in every stage of the activity, from preparation to the main implementation. Furthermore, the sea harvest tradition encompasses various educational aspects that can be utilized as learning resources in high school history lessons, including spiritual, social, cultural, and historical aspects. This tradition demonstrates the continuity of cultural values and practices passed down from previous generations, making it a contextual and relevant resource for local history learning in students’ lives.